Chromosomal analysis and short-term outcome of prenatally diagnosed congenital heart disease - Marcellino Verbeke; Laurens Hannes; Koen Devriendt; Kris Van den Bogaert; Bjorn Cools; Luc De Catte; Marc Gewillig; Jeroen Breckpot (Scientific Reports, 2025)
Abstract Congenital structural heart disease (CHD) is the leading cause of infant death from birth defects. Postnatal survival primarily depends on the type and severity of the defect. In addition, worse cardiac prognosis is observed when extra-cardiac anomalies (ECA) are associated. This retrospective chart review was aimed at finding markers for short-term outcome prediction of prenatally-diagnosed complex CHD, focusing in particular on the impact of CHD category, of CHD severity score and of prenatal or postnatal diagnosis of ECA or chromosomal anomalies on 4 primary outcomes: termination of pregnancy (TOP), intrauterine fetal demise, neonatal mortality and 1-year-survival rate. We reviewed medical files from 381 fetuses, presenting at our center between 2018 and 2021 with CHD for which prenatal advice by a pediatric cardiologist was sought. 341 fetuses met the inclusion criteria for the study. Twin pregnancies (7.62%; OR 4.76 (p < 0.001)) and pregnancies resulting from assisted reproductive technology (7.33%; OR 2.44 (p < 0.001)) were more prevalent compared to the general population. CHD categories and CHD severity scores, ranging from A (extremely high risk based on CHD or ECA type) to D (low risk), were assigned to each fetus. Prenatal or postnatal chromosomal microarray results were available for 232 fetuses (68%) and were abnormal in 30 (12.9%). Logistic regression analysis was used to determine significant predictors for the primary outcomes ‘TOP’, ‘postnatal demise before the age of 1 month’ and ‘survival at the age of 1 year’. TOP was carried out significantly more with: prenatal genetic diagnosis, severity score A and severity score B. Interestingly, a prenatal genetic diagnosis was negatively correlated with pregnancy continuation, but it was not a significant predictor for postnatal mortality, while a postnatal diagnosis of a genetic disorder impacted early but not late postnatal mortality. In addition, postnatal mortality both before the age of 1 month or before the age of 1 year was significantly associated with lower postmenstrual age at birth, CHD severity score B and major ECA at birth. These results underscore the importance of genotyping and of accurate cardiac and extracardiac phenotyping for prognostication in fetuses with CHD.